2022
DOI: 10.1073/pnas.2209132119
|View full text |Cite
|
Sign up to set email alerts
|

Spatial turnover of soil viral populations and genotypes overlain by cohesive responses to moisture in grasslands

Abstract: Viruses shape microbial communities, food web dynamics, and carbon and nutrient cycling in diverse ecosystems. However, little is known about the patterns and drivers of viral community composition, particularly in soil, precluding a predictive understanding of viral impacts on terrestrial habitats. To investigate soil viral community assembly processes, here we analyzed 43 soil viromes from a rainfall manipulation experiment in a Mediterranean grassland in California. We identified 5,315 viral populations (vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 93 publications
8
46
0
Order By: Relevance
“…Recent advances have demonstrated that soil virus communities are dynamic in a wide range of soils [e.g. 8 , 9 ] and augmenting virus loads modulate C and N fluxes [ 10 , 11 ]. Nevertheless, identifying active interactions with specific populations or functional groups in soil remains challenging due to structural complexity and the vast diversity of hosts and viruses.…”
mentioning
confidence: 99%
“…Recent advances have demonstrated that soil virus communities are dynamic in a wide range of soils [e.g. 8 , 9 ] and augmenting virus loads modulate C and N fluxes [ 10 , 11 ]. Nevertheless, identifying active interactions with specific populations or functional groups in soil remains challenging due to structural complexity and the vast diversity of hosts and viruses.…”
mentioning
confidence: 99%
“…Comparisons of active (e.g., RNA) and total (DNA) microbiomes 60 are worth more extensive exploration over spatiotemporal scales in soil. Substantial viral community diversity and heterogeneity over time, space, and environmental conditions are emerging as the rules in soil [11][12][13][14][15][16][17][18] , begging the question, how is this extreme viral diversity maintained? Viral survival in soils that experience seasonal drought, such as those studied here, is particularly mystifying.…”
Section: Discussionmentioning
confidence: 99%
“…With up to 10 10 viral particles per gram of soil, viruses are assumed to be influential in terrestrial ecosystems too [5][6][7][8][9][10] , but viral impacts on soil ecology and biogeochemistry are just beginning to be explored. Although methodological barriers for soil viral community analyses have largely been overcome [10][11][12][13] , the recent advent of large-scale viral sizefraction metagenomics (viromics) in soil has heralded new challenges associated with extreme soil viral diversity 12,[14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations